2012
DOI: 10.2147/ijn.s26882
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1-expressing adipose stem cells genetically modified with baculovirus nanocomplex: investigation in rat heart with acute infarction

Abstract: Abstract:The objective of this study was to develop angiopoietin-1 (Ang1)-expressing genetically modified human adipose tissue derived stem cells (hASCs) for myocardial therapy. For this, an efficient gene delivery system using recombinant baculovirus complexed with cell penetrating transactivating transcriptional activator TAT peptide/deoxyribonucleic acid nanoparticles (Bac-NP), through ionic interactions, was used. It was hypothesized that the hybrid Bac-NP Ang1 system can efficiently transduce hASCs and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Angiopoietin-1 is an important pro-angiogenic factor involved in vascular maturation and neovasculogenesis. Similar to what was described for VEGF, genetically modified MSC expressing angiopoietin-1 were more effective in regenerating myocardial tissue after infarction than MSC alone [ 39 ]. Liu and coworkers also demonstrated that MSC expressed functional receptors for angiopoietin-1 and that angiopoietin-1 protected MSC against apoptosis induced by hypoxia and serum deprivation [ 40 ].…”
Section: Discussionmentioning
confidence: 81%
“…Angiopoietin-1 is an important pro-angiogenic factor involved in vascular maturation and neovasculogenesis. Similar to what was described for VEGF, genetically modified MSC expressing angiopoietin-1 were more effective in regenerating myocardial tissue after infarction than MSC alone [ 39 ]. Liu and coworkers also demonstrated that MSC expressed functional receptors for angiopoietin-1 and that angiopoietin-1 protected MSC against apoptosis induced by hypoxia and serum deprivation [ 40 ].…”
Section: Discussionmentioning
confidence: 81%
“…Angiopoietin-1 (Ang1) can significantly promote neovascularization via the inhibition of leukocyte-endothelium interactions and endothelial permeability,2 and during this course, vascular endothelial growth factor (VEGF) might be released from genetically modified adipose stem cells 7. Xu, et al8 reported that LPS-induced lung injury was alleviated in mice treated with BM-MSCs (from bone marrow, BM) carrying Ang1 (MSCs-Ang1), compared with mice treated with only MSCs or Ang1 in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…The viral surface has been chemically modified to form cationic nanostructures, similar to our earlier studies232425, for local delivery of human vascular endothelial growth factor-A 165 (Vegf) therapeutic genes to attenuate ISR26. Insect cell host-specific baculovirus (Bac) offers a unique advantage over other gene delivery systems because of its ability to efficiently transduce non-dividing cells, inherent inability to replicate in mammalian cells, low cytotoxicity even at high viral dosage, absence of preexisting antibodies against Bac in animals and also easy production scale up to high viral titre2728.…”
mentioning
confidence: 97%